Piezoelectric based energy harvesting interface circuit - Md Khir, Qurratuaini Shahidah (2017)
In this study focused on solving the issue of conventional power plant that require large space, immovable, polluting and expensive by employing abandoned energy produce by mechanical vibration in the environment. The piezoelectric based energy harvesting interface circuit is the main focus of this study and as it produce low voltage, the study include the investigation of Direct Current - Direct Current (DC-DC) converter topologies to improve the outcome. The piezoelectric energy harvesting prototype include piezoelectric transducer, rectifier, converter, Arduino Uno microcontroller and water wave tank. A boost converter with variable duty cycle was designed to improve the output voltage range from 1.5 V to 6 V. The size of piezoelectric transducer disc used in this study varies from 20 mm, 27 mm and 35 mm. The outcomes from the energy harvesting device was determined through measurement using digital multimeter and oscilloscope. It was found that higher duty cycle produce higher output. The combination of large boost converter duty cycle, 0.845, and large size of piezoelectric transducer, 35 mm, has produced the highest output. The measured input voltage and output voltage were 0.94 V and 6.4 V per tap respectively. The calculated output energy was 4.5 mJ per tap. The prototype piezoelectric energy harvesting circuit has successfully produce the output voltage in the range of 1.5 V to 6 V.